Estudio arqueométrico de la cerámica de los estilos Castillo Modelado e Inciso procedente de las Huacas de Moche y Huaca las Estrellas en el valle de Moche y Castillo de Tomabal en el valle de Virú - Mejia Aranguren, Luisa Raquel (2020)
ABSTRACT The present investigation focuses on the comparative study of the ceramic material of the Castillo Modelado and Inciso styles from the archaeological sites Huacas de Moche, Huaca Las Estrellas and Castillo de Tomabal. The inclusion of clay samples from the Moche and Virú quarries was fundamental at the compositional level during the process of multivariate statistical analysis, after the application of the X-ray fluorescence analytical technique (FRX). The results showed that Castillo Modelado and Inciso styles were imported from the Virú Valley to sites in the Moche Valley such as Huacas de Moche and Huaca Las Estrellas, but then they were copied and produced locally. These styles would have an autonomous character in relation to the elitist Virú-Gallinazo and Mochica styles. Indeed, it would be a domestic ceramic tradition of the North Coast of Peru and, therefore, should not be considered by itself as a cultural marker to determine settlements of Viru-Gallinazo affiliation in the different valleys of the northern coast of Peru.